The use of the saber in the army of Napoleon - Gevaert Bert (Acta Periodica Duellatorum)
Though Napoleonic warfare is usually associated with guns and cannons, edged weapons still played an important role on the battlefield. Swords and sabers could dominate battles and this was certainly the case in the hands of experienced cavalrymen. In contrast to gunshot wounds, wounds caused by the saber could be treated quite easily and caused fewer casualties. In 18th and 19th century France, not only manuals about the use of foil and epee were published, but also some important works on the military saber: de Saint Martin, Alexandre Muller… The saber was not only used in individual fights against the enemy, but also as a duelling weapon in the French army.